2022
DOI: 10.1029/2022ja030870
|View full text |Cite
|
Sign up to set email alerts
|

Dependencies of GPS Scintillation Indices on the Ionospheric Plasma Drift and Rate of Change of TEC Around the Dawn Sector of the Polar Ionosphere

Abstract: The dependencies of global positioning system (GPS) scintillation indices on ionospheric plasma flow and the rate of change of total electron content (TEC) around the dawn sector for the first time of the polar ionosphere are investigated. The phase scintillation index (σφ) derived from GPS measurements of the Canadian High Arctic Ionospheric Network (CHAIN) shows linear dependencies on both the plasma drift speed measured by the SuperDARN radar and on the rate of change of TEC estimated from the GPS receivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The correlation between σ ϕ,1min and |∆TEC| suggests that much of the elevated σ ϕ,1min is refractive due to time-varying TEC. Wang et al (2022) showed that σ ϕ is correlated with the drift speed of plasma, and they concluded that localized TEC structures drift across the LOS of each GPS satellite-receiver pair and increase σ ϕ . In the present study, enhanced σ ϕ,1min was indeed located in the region of enhanced flows but the enhanced flows were also found in the regions without enhanced σ ϕ,1min (Figure 1c).…”
Section: Scintillation Evolution: 1-min Scintillation Indicesmentioning
confidence: 99%
See 2 more Smart Citations
“…The correlation between σ ϕ,1min and |∆TEC| suggests that much of the elevated σ ϕ,1min is refractive due to time-varying TEC. Wang et al (2022) showed that σ ϕ is correlated with the drift speed of plasma, and they concluded that localized TEC structures drift across the LOS of each GPS satellite-receiver pair and increase σ ϕ . In the present study, enhanced σ ϕ,1min was indeed located in the region of enhanced flows but the enhanced flows were also found in the regions without enhanced σ ϕ,1min (Figure 1c).…”
Section: Scintillation Evolution: 1-min Scintillation Indicesmentioning
confidence: 99%
“…Traditionally, scintillation is characterized by the phase and amplitude scintillation indices that measure variation of GNSS signals (at a sampling of tens of Hz) after detrending them at a cutoff frequency of 0.1 Hz. High‐latitude scintillation is often seen only in the phase of the radio signal without amplitude scintillation (Doherty et al., 2000; Jiao et al., 2013; Sreenivash et al., 2020; Wang et al., 2022). Many works consider that the elevated phase scintillation index means scintillation, but a caution should be raised for the interpretation of the scintillation indices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancements in σ Φ indices have also been shown to be adequately represented by ROTI on larger scales above the Fresnel scale (Rino et al, 2019), and can additionally be dependent on the plasma flow and rate of change of TEC (ROT) at high latitudes (Y. Wang et al, 2018Wang et al, , 2022. Recent literature has proposed that only fluctuations of the former nature, namely of stochastic nature, are deemed scintillations (De Franceschi et al, 2019;Ghobadi et al, 2020;McCaffrey & Jayachandran, 2019;Spogli et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Within this scale range, the rate of total electron content (TEC) change index (ROTI) has recently been shown by Rino et al (2019) to give some good hints about possible stochastic features of ionospheric effects caused by large-scale and medium-scale structures. Most of the recent research on the GNSS scintillation has been dedicated to efficiently evaluate the diffractive and refractive contribution in the recorded GNSS fluctuations, especially in the high-latitude ionosphere, where the highly dynamic plasma complicates such a task (Conroy et al, 2022;Ghobadi et al, 2020;McCaffrey & Jayachandran, 2019;Spogli et al, 2021;Wang et al, 2018Wang et al, , 2022. In this study, we investigate the role of the particle precipitation in small-scale plasma structuring in the E and F-region ionosphere and its effects on trans-ionospheric radio wave propagation over Svalbard (Norway).…”
mentioning
confidence: 99%